INCREMENTO DE LA PENA EN CASO DE ACUSACIÓN O DENUNCIA MALICIOSA JUDICIALMENTE DECLARADA EN EL DELITO DE VIOLACIÓN - Criollo Castro, Juan Carlos (2019)
The interest to develop the present thesis that title: "INCREASE OF THE PENALTY IN CASE OF ACCUSATION OR MALICIOUS DENOUNCE JUDICIALLY DECLARED IN THE CRIME OF VIOLATION", arose with the analysis and study of the legal norm concerning the crimes of major commotion, transcendence and social interest, since when cataloged in this way and knowing that a high commitment index is established in our society, it is also necessary to highlight the damages caused to people when we refer to maliciously denouncing the false commission of these as later I make specific reference to the crime of rape. The crime of Rape, which is punishable under the Comprehensive Organic Code, article 171, sanctions the commission thereof with imprisonment from nineteen to twenty-two years and in some cases with aggravating circumstances that deprive the responsible party of liberty for up to twenty-six years. The same legal body in its article 271 Malicious Accusation or Denunciation makes it possible to demonstrate that its regulations violate the Principle of Proportionality between the penalty and the crime, for which it allows the violation of a number of constitutional rights included in Article 66 Rights of Freedom. Despite the constitutional guarantees that the Constitution establishes for all people, I have been able to corroborate in my investigation that there is no 6 specific legal regulation that sanctions the accusation or malicious denunciation declared judicially for the crime of rape. Therefore, I conclude that accusing or maliciously reporting a violation severely undermines the rights of liberty of people who are innocent and that prior to these false accusations they developed their lives normally and protected their personal integrity, honor, good name, and the non-discrimination of their rights, for which this investigation deserves to be sanctioned with these behaviors with greater rigor. The violation of these rights to which I mention in the previous paragraphs, happens in Ecuador especially, because there are no rules designed to punish rigorously those responsible for these behaviors, this legal insufficiency is causing the problem I have addressed in the present work, which is a problem of a social nature because in comparison to other legislations of countries on which I base my work with comparative law, damaging honor, violating the personal integrity and the good name of someone sanctions with deprivation of rigorous freedom and comprehensive reparations in all its characters and because these situations are something that has been transcending with the passage of time in our society, it is necessary to establish strict penalties for these behaviors since in one way or another they would contribute as a constraint and give back to correct the damages caused to people who were accused without foundation any. In the execution of the study all the steps established in the Regulations of the Academic Regime of the National University of Loja are fulfilled, for which it includes the following parts: title, summary in Spanish and English, introduction, review of literature, materials and methods, results, conclusions, recommendations, and finally, a proposal for legal reform to the Comprehensive Criminal Organic Code.